2006
DOI: 10.1002/aqc.799
|View full text |Cite
|
Sign up to set email alerts
|

Culturing freshwater pearl mussel Margaritifera margaritifera: a breakthrough in the conservation of an endangered species

Abstract: ABSTRACT1. The freshwater pearl mussel Margaritifera margaritifera L. is globally endangered and is threatened by commercial exploitation, pollution and habitat loss throughout its range. Captive breeding would be a valuable tool in enhancing the status of M. margaritifera in the UK.2. We have developed a semi-natural system for successfully infecting juvenile brown trout with glochidial M. margaritifera, and culturing juvenile mussels in experimental tanks where glochidial M. margaritifera can excyst from fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 10 publications
0
72
0
Order By: Relevance
“…Wilson et al 2005, Robson et al 2007. Given that the minimum appropriate sampling frequency has now been established for recording fine-scale Margaritifera margaritifera gape and, most probably, pumping behaviour, our ongoing research can test if the breakthrough in the ability to culture M. margaritifera (Preston et al 2007) can be further improved by conditioning broodstock and providing juveniles with additional food. Advances in the understanding of bivalve feeding and reproductive strategies may be gleaned by recording behaviour with high temporal and sensor resolution over a range of ecological circumstances (according to factors such as depth, light, temperature, particulate matter, food availability and predator interactions) and may aid long-term survival of endangered bivalves including freshwater pearl mussels.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al 2005, Robson et al 2007. Given that the minimum appropriate sampling frequency has now been established for recording fine-scale Margaritifera margaritifera gape and, most probably, pumping behaviour, our ongoing research can test if the breakthrough in the ability to culture M. margaritifera (Preston et al 2007) can be further improved by conditioning broodstock and providing juveniles with additional food. Advances in the understanding of bivalve feeding and reproductive strategies may be gleaned by recording behaviour with high temporal and sensor resolution over a range of ecological circumstances (according to factors such as depth, light, temperature, particulate matter, food availability and predator interactions) and may aid long-term survival of endangered bivalves including freshwater pearl mussels.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of pearl mussels, the availability of culturing techniques has been considered a breakthrough in their conservation (Preston et al, 2007). Preservation of genetic diversity requires robust genetic analyses of source populations.…”
Section: Genetic Population Structure and Mussel Propagationmentioning
confidence: 99%
“…In flow-through systems, mussel broodstock can be maintained in salmonid hatchery troughs supplied with filtered river water (30 µm) to reduce sediment loads, and covered with sand and gravel (Hastie & Young 2003a, Preston et al 2007). Very little is known about the diet requirements of adult Margaritifera margaritifera, although information from other freshwater bivalves suggests that they probably feed on freshwater algae within the 15 to 40 µm range (Winkel & Davids 1982).…”
Section: Fertilisation Of Females In Captivitymentioning
confidence: 99%
“…As an alternative to the cohabitation method, the outflow of tanks housing gravid mussels can be diverted into fish tanks housing hatchery-reared juvenile salmonids (Hastie & Young 2003a, Preston et al 2007). Hastie & Young (2001, 2003a showed that large numbers of Atlantic salmon and brown trout could be infected in this way, with glochidia loads ranging between 10 and 800 glochidia per fish.…”
Section: Encystment Of Glochidiamentioning
confidence: 99%
See 1 more Smart Citation